Permodelan Struktur Bawah Basement Ruang Terbuka Hijau Menggunakan Metode Building Information Modeling - Duna, Anaknda Fauzan Syahrani; Purwantoro, Almuntofa (Jurnal Basement : Jurnal Teknik Sipil, 2026)
The rapid development of the construction industry demands innovation in planning methods that can improve effectiveness and efficiency in project delivery. The increasing complexity of construction projects requires planners to adopt systems capable of managing information accurately and in a well-coordinated manner. However, in practice planners still rely on conventional 2D-based methods, which have the potential to cause inefficiencies and errors during project execution. Along with technological advancements, Building Information Modelling (BIM) has emerged as a method considered effective and efficient in the planning process. BIM-based modeling is capable of producing integrated 3D visualizations and providing detailed and accurate information related to building elements compared to conventional methods. The objective of this study is to develop a model of the substructure, including basement walls, basement slabs, and pile caps, for the Green Open Space (RTH) project at Ex Koni, Palangka Raya City. The design method applied in this research is based on Building Information Modelling using Autodesk Revit software. The data used in this study are secondary data in the form of Detail Engineering Design (DED). The results of this study indicate that the application of BIM produces a substructure model along with detailed information presented in an integrated 3D model.